2019
DOI: 10.1002/anie.201905439
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Quantitative Descriptor of the Dispersion Interaction Potential

Abstract: London dispersion, universally attractive forces originating from fluctuating dipoles,i so mnipresent in molecules.W hile its understanding has recently made tremendous progress,i ts general appreciation is still lagging behind electrostatics.T his can be explained by the simple tools available to study electrostatic interactions,such as electrostatic potential (ESP) maps and partial charges,a nd al ackt hereof for dispersion. We herein report au niversal quantitative descriptor of dispersion interaction poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 126 publications
2
47
0
Order By: Relevance
“…We additionally employed LD potential maps developed by Pollice and Chen to visualize these LD interactions (Supporting Information, Figure S2). [16] These confirm the conclusions drawn from the qualitative NCI analysis.…”
Section: Reconsidering Steric Effectssupporting
confidence: 81%
“…We additionally employed LD potential maps developed by Pollice and Chen to visualize these LD interactions (Supporting Information, Figure S2). [16] These confirm the conclusions drawn from the qualitative NCI analysis.…”
Section: Reconsidering Steric Effectssupporting
confidence: 81%
“…The most conservative means of estimating such an error is to attribute the entire difference between the electrostatic interaction energies of 4 a and 4 b as arising from non‐transferrable hydridic repulsion, and to propagate this difference through all dependent dissected electrostatic and interaction energies (gray and black error bars in Figure , respectively). Even after making such a conservative error estimate, the total energy of the Au⋅⋅⋅Au interaction is found to be small in comparison to the ligand⋅⋅⋅ligand interactions that also occur within the dimer complex (Figure B, bottom), Consistent with recent examinations of aurophilic and stacking interactions, the energy decomposition analysis revealed that dispersion is the dominant attractive component in all of the stacked dimer fragments, but not the [Au] 2 dimer. Instead, the dissection suggests that the main stabilizing forces in the [Au] 2 dimer arise from either electrostatic or orbital interactions.…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that Et SbNMe2 could have formed via decomposition of a free rotation around the metal-nitrogen bonds allows overlap of the nitrogen lone pairs with metal-centred acceptor orbitals. Attractive dispersion forces 29 between the bulky trialkylsilyl groups (known to be excellent dispersion donors) 30 also play a significant role in stabilizing Et BiSb Et (∆Edisp = -39.03 kcal mol -1 ). Consistently, Bader's Atom-In-Molecules (AIM) 31 analysis detected numerous bond paths (Figure 1c, vertical green lines) and bond critical points (red dots) between the ligands on each metal showing peripheral attractive interactions between the bulky ligands.…”
mentioning
confidence: 99%